Homeward bound II lost in San Francisco - Jossen, Barry; Ellis, David R. (USA: Walt Disney Pictures [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor])
Now feisty bulldog, Chance pampered cat Sassy and lovable golden retriever Shadow are lost in the bustling city of San Francisco
Editor, Michael A. Stevenson, Peter E. Berger ; photography, Jack Conroy
Keywords: Animal films; Dogs in motion pictures